Desolation code [compact disc, unabridged] - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. Kurt Austin adventures., 2024)
When Kurt Austin and Joe Zavala investigate a mass stranding of aquatic life in the Indian Ocean, they accidentally uncover a much deeper mystery. A strange figure soon steals NUMA's findings, forcing a high-speed chase, someone really didn't want them examining those dead whales. But who, and why? A cryptic text through the NUMA satellite network makes things still stranger: these odd phrases and numbers look like NUMA codes. But who could be tantalizing the crew with such specific knowledge of their tech? Are they being helped by an old friend, or lured into a trap by a traitor who knows a little too much about NUMA's inner workings? Kurt, Joe, and even Max, the agency's supercomputer, will have to investigate like never before as they decrypt data, infiltrate a cult of cloned men, and prepare for a battle on two very different planes: one physical; one digital. The aquatic stranding was just the beginning of a sinister plan concocted by a mind more brilliant than any they've ever faced, the mind of a machine. A new, terrifying world order is being plotted. First marine ecosystems will be devastated, then the entire globe's. Unless the NUMA crew can stop this code of desolation.